Credit card behavior as a function of impulsivity and mother’s socialization factors - Henegar, Justin M.; Archuleta, Kristy L.; Grable, John; Britt, Sonya L.; Anderson, NaRita; Dale, Anita (My University, 2014)
The current paper, using data from the National Longitudinal Survey of Youth 1979 (NLSY) and the NLSY Child Survey, reports results from a test designed to determine if impulsiveness is associated with credit card behavior, and whether a mother?s time preference, socioeconomic status, and risk attitude transmit to her children in shaping credit card behavior. In addition to certain demographic factors, individuals who exhibited self-control/ low impulsivity were more likely to possess a credit card, as were those whose mothers had a high socioeconomic status. Men, those with higher income, and those who were raised by mothers with high financial impatience were more likely to hold a credit card balance.
Keywords: Credit cards; Impulsivity; Socialization theory; Socioeconomic status